MECHANICAL PROPERTIES ENHANCEMENT OF BORON CARBIDE BASED ARMOUR MATERIALS - Priyadi Hartoko; Sean Li (The Republic of Indonesia Defense University, 2020)
Lightweight armor materials made from ceramics have become a great interest in the past decades. There have been many research efforts to develop the high-performance ceramics for this particular application. Boron carbide (B4C) is one of the promised candidates due to its extraordinary hardness, wear resistance, chemical inertness, ultra-lightweight, and its high resistance to radiation. However, the strong covalent bonding nature of B4C makes it hard to be sintered. Sintering at high temperatures and the presence of impurities can also result in grain coarsening. One of the methods being used to overcome the problems is to introduce Boron (B) as a sintering aid into raw materials of B4C. To evaluate the effects of B addition on the sinterability of B4C, B4C powders were ball-milled with B powders in different ratios and the mixtures of B4C and B were processed by spark plasma sintering technique. Density and toughness of the as-sintered materials were increased along with increasing B content in the range from 1 wt% to 7 wt% while hardness and strength of the samples were also increased when the percentage of B addition is up to 5 wt%.